Two Are Better Than One : Leveraging Resources across Advisory Business Lines - Nasibov, Arif; Khodjaev, Elbek (World Bank, Washington, DC, 2012)
In 2008, Uzbekistan significantly improved its rank in the doing business 'getting credit" indicator, moving up 38 positions from the previous year, and by July a draft law titled, 'On Sharing Credit Information," which meets best international standards, was developed by a six-member working group, including International Finance Corporation (IFC) staff and two regulators from the Central Bank of Uzbekistan (CBU). Pending the draft law's passage by the Parliament of Uzbekistan, this major achievement will significantly improve the still-developing regulatory environment in this sphere. These results were achieved thanks to a common approach and efforts of two IFC advisory services projects: the Uzbekistan Business Enabling Environment Project (UzBEE) and the Azerbaijan Central Asia Leasing Facility (ACALF) Project. In this smart lesson, the authors describe experience in carrying out joint activities between two different IFC projects and the lessons learned for how to assure successful cross-project collaboration by building an enthusiastic team and assigning clear objectives to individuals.